Uzbekistan - Sophie Ibbotson; Max Lovell-Hoare (USA the Bradt Travel Guide, 2020)
Written and updated by expert authors who have extensive experience of living and working in Central Asia, this new, fully updated third edition of Bradt's Uzbekistan remains the definitive and only standalone practical travel guide to this increasingly liberal destination - central Asia's most populous country and the heart of the Silk Road. Offering more detail for independent travellers than any other guidebook, it includes first-hand descriptions of everything from UNESCO world heritage sites and the world's best collection of Russian avant-garde art, to riding across deserts by camel and cooking plov.The quintessential Silk Route destination, Uzbekistan is opening up to tourism, easing visa regulations, encouraging family-owned guesthouses, building new railways (including a tunnel to the Fergana Valley) and introducing high-speed trains. With the passing of the post-Soviet strongman Islam Karimov and the election of a more reformist leader, there is an air of change about the country.This new edition includes expanded coverage of hiking, details of new entertainment such as the sound and light show in the Registan in Samarkand, and lots of new practical information, ranging from the increasing availability of ATMs to efforts to develop tourism, visa requirements, availability of SIM cards, haggling for taxis, access to museums and booking accommodation. New maps have also been added and existing maps revised and expanded as appropriate.Whether you're interested in culture, trekking, historical sites, archaeology and architecture, seeing endless deserts or the majestic mountainscapes of the Tien Shan range, or simply fascinated by the golden road to Samarkand and the equally famous Silk Road cities of Bukhara and Khiva, Bradt's Uzbekistan is the ideal companion.
Keywords: Travel; (ETB-2001) A Sense of Place